Efektifitas Penerapan Sistem Persidangan Elektronik E-Court dalam Pengadilan Negeri Pamekasan - R.Moh Hilman Wahyudi; Mohammad Hosen (Jurnal Hukum dan Sosial Politik, 2024)
E-court is a court instrument as a form of service to the public in terms of registering cases carried out by the parties online, estimating court costs electronically, paying downpayments online, summoning online and sending court documents online. The purpose of this research to study the effectiveness of implementing e-court electronic trials in the Pamekasan District Court. This study uses normative legal research methods. The statutory and conceptual approaches are the approaches used in this research. The collection of legal materials in this journal uses library research. The method of analysis of legal materials used in this journal refers to deductive, namely drawing conclusions from a general problem to the concrete problems faced. The results of this research show that there are advantages and disadvantages in implementing electronic trials in the Pamekasan district court and the need for them. Further adaptation by the community in the latest innovations in case handling. In accordance with Perma No. 1 of 2019.